PENGARUH IMPLEMENTASI ABSENSI FINGERPRINT, SANKSI, DAN MOTIVASI TERHADAP DISIPLIN KERJA KARYAWAN DI INTAKO - Nafa Putri Maulidya; Ayu Lucy Larassaty; Wahyu Eko Pujianto (Universitas Nahdlatul Ulama Sidoarjo, 2021)
This study aims to determine the effect of Fingerprint Attendance Implementation, Sanctions and Motivation on Employee Work Discipline at INTAKO Tanggulangin Sidoarjo. The number of respondents used in this study were as many as 40 employees using the saturated sample technique. The research data collection technique is by distributing questionnaires and interviews. The research method used in this research is quantitative method, using analysis tools SPSS version 20 then perform statistical calculations in the form of validity and reliability tests. Hypothesis testing in this study used data analysis tools in the form of classical assumption test, multiple linear regression, simultaneous test (F test), partial test (T test), and the coefficient of determination. The results of this study indicate that simultaneously the variables of fingerprint attendance, sanctions and motivation together have an effect on the work discipline of employees of INTAKO Tanggulangin Sidoarjo. Whereas partially the implementation of fingerprint attendance and sanctions has no effect on the work discipline of employees of INTAKO Tanggulangin Sidoarjo, while motivation has a positive effect on work discipline of employees of INTAKO Tanggulangin Sidoarjo.